α-glucosidase Inhibition, DPPH Scavenging activities and Chemical Analysis of Polysaccharide Extracts from Aquilaria sp. Leaves - Zalilawati, Mat Rashid; Nor Hasima, Mahmod; Nur Nasyitah, Mohd Nasir (2020)
Aquilaria sp. belongs to Thymelaeaceae family. This genus produces a unique fragrant wood locally known as ‘gaharu’. It is well known for usages in aromatherapy while very few scientific evidence on its usage as herbal medicine have been published. The current study was therefore conducted to determine the chemical characteristics as well as antioxidant and α-glucosidase inhibition potential of carbohydrate-rich extracts (aqueous and polysaccharide extracts) from three Aquilaria species leaves (A. malaccensis, A. sinensis and A. subintegra). The isolation of polysaccharide (PS) from the aqueous extract (AE) was conducted by ethanol precipitation prior to ultrasonic-assisted extraction. The total phenolic content (TPC), proximate and Fourier Transform Infrared Spectroscopy (FTIR) analysis were carried out to investigate the chemical characteristics, while the bioactivities determined were 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging and αglucosidase inhibition. As a result, AE of A. malaccensis leaves showed the strongest α-glucosidase (IC50: 0.038 mg/mL) and DPPH (IC50: 0.084 mg/mL) inhibition while contained more TPC (61.16 mg GAE/g) compared to other two species. Furthermore, PS of A. malaccensis leaves displayed even stronger α-glucosidase inhibition (IC50: 0.014 mg/mL) compared to its respective AE and other PS. In conclusion, this study primarily revealed the scientific evidence on the bioactive potential of PS of Aquilaria sp.